Calamus vitiensis (ARECACEAE), A NEW RECORD OF RATTAN IN SUMBAWA ISLAND, INDONESIA - Himmah Rustiami; Lulut Dwi Sulistyaningsih (SEAMEO BIOTROP, 2019)
Calamus vitiensis, previously known to occur only in Papua New Guinea, Australia (Queensland), the Solomon Islands, Vanuatu, and Fiji is now also found in the mountainous area of Batudulang, West Sumbawa, Lesser Sunda Islands, Indonesia. This paper presents a complete report of the description, notes, and illustrations of the species.